The Intel trinity : how Robert Noyce, Gordon Moore, and Andy Grove built the world's most important company /: how Robert Noyce, Gordon Moore, and Andy Grove built the world's most important company. (2014) - Malone, Michael S (Michael Shawn), 1954-
No abstract available